Обряд "Калоян" у румуномовного населення Буковини - Мойсей, А. (Народна творчість та етнографія, 2006)
Ethno-folkloric tradition of the eastern Romanians preserved such rituals that bear the features of the outlook of lndo-E.uropeans or even of the primitive agriculturists. This includes a complex of pluvial observances (Kalojan, Mother of rain, Paparuda, etc.) that are syncretic in their structure and symbolic in the semantics. Basing on the previous investigations of other scholars and on the field work the author describes Kalojan — a symbolic funeral of an anthropomorphic doll, - its versions in different parts of the region, etymology, etc.